SOX2–LIN28/let-7 pathway regulates proliferation and neurogenesis in neural precursors - Cimadamore, Flavio (National Academy of Sciences, 2013)
The transcription factor SRY (sex-determining region)-box 2 (SOX2) is an important functional marker of neural precursor cells (NPCs) and plays a critical role in self-renewal and neuronal differentiation; however, the molecular mechanisms underlying its functions are poorly understood. Using human embryonic stem cell-derived NPCs to model neurogenesis, we found that SOX2 is required to maintain optimal levels of LIN28, a well-characterized suppressor of let-7 microRNA biogenesis. Exogenous LIN28 expression rescued the NPC proliferation deficit, as well as the early but not the late stages of the neurogenic deficit associated with the loss of SOX2. We found that SOX2 binds to a proximal site in the LIN28 promoter region and regulates LIN28 promoter acetylation, likely through interactions with the histone acetyltransferase complex. Misexpression of let-7 microRNAs in NPCs reduced proliferation and inhibited neuronal differentiation, phenocopying the loss of SOX2. In particular, we identified let-7i as a novel and potent inhibitor of neuronal differentiation that targets MASH1 and NGN1, two well-characterized proneural genes. In conclusion, we discovered the SOX2–LIN28/let-7 pathway as a unique molecular mechanism governing NPC proliferation and neurogenic potential.